(untitled) (International Journal of Engineering and Computer Science, 2015)
— Wireless communication technology is emerging very fast with reliable communication lead to emergence of very numerous technologies. There are various modulation schemes suitable in optical wireless communication like OOK, PPM, DPIM, DHPIM, and OFDM. As modulation techniques is categorized into bandwidth & power efficient but for error performance there are few assumptions where there is no bandwidth limitation. In this paper we analyze the error rate in AWGN channel for these modulation techniques & the combined result shows that DPIM, DH-PIM & OFDM are applicable for future applications.